Flouting Maxim Analysis in "Stranger Things 3" Television Series: Pragmatics Approach - Triyani Tami; Nurma Dhona Handayani (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This research was descriptive qualitative research, in which the data were utterances in the form of sentences, clauses, and words. They were collected through non-participant observation and analyzed by the pragmatic identity analysis. This research aimed to find the types and the strategies of flouting maxims used by the characters in a television series, Stranger Things 3. The main theory used in conducting this research was the theory purposed by Grice to investigate the types of flouting maxim and the theory of Cutting for the strategies used in flouting the maxim. From the observation it was found that there were 16 utterances indicate the flouting maxims. They were 1 datum of flouting the maxim of quality, 3 data of flouting the maxim of quantity, 5 data of flouting the maxim of manner, and 7 data of flouting the maxim of relation. It also found that 5 of 8 strategies were used in Stranger Things 3.